2021
DOI: 10.3390/fishes6040070
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Parvalbumin Genes in Teleost Fishes after the Whole-Genome Duplication

Abstract: Parvalbumin is considered a major fish allergen. Here, we report the molecular evolution of the parvalbumin genes in bony fishes based on 19 whole genomes and 70 transcriptomes. We found unexpectedly high parvalbumin diversity in teleosts; three main gene types (pvalb-α, pvalb-β1, and pvalb-β2, including oncomodulins) originated at the onset of vertebrates. Teleosts have further multiplied the parvalbumin gene repertoire up to nine ancestral copies—two copies of pvalb-α, two copies of pvalb-β1, and five copies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 68 publications
4
15
0
Order By: Relevance
“…Furthermore, this study also provided insight on the evolution of parvalbumin in vertebrates. Similar to the previous finding, we discovered three groups of parvalbumins in Teleost 23 . Based on the sequence homology with BLAST algorithm, we described one group as thymic CPV3-like subtype which reported to be found in lower vertebrates and related to oncomodulin (a type of β-parvalbumin) in mammals 24 .…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, this study also provided insight on the evolution of parvalbumin in vertebrates. Similar to the previous finding, we discovered three groups of parvalbumins in Teleost 23 . Based on the sequence homology with BLAST algorithm, we described one group as thymic CPV3-like subtype which reported to be found in lower vertebrates and related to oncomodulin (a type of β-parvalbumin) in mammals 24 .…”
Section: Discussionsupporting
confidence: 91%
“…Phylogenetic tree analyses readily distinguish ancient -parvalbumin and oncomodulin lineages that are represented in all clades of investigated jawed vertebrates (Figure 4 and Supplementary File S4). This agrees with findings by, for example, Modrell et al, 2016 [25], and Mukherjee et al, 2021 [26], who both named the oncomodulin lineage the "1" The tree is drawn to scale, with branch lengths measured in the number of substitutions per site. Clusters with teleost sequences (including sometimes also nonteleost sequences) are condensed; for a non-condensed tree and full descriptions see Supplementary File S4A.…”
Section: The Overall Phylogeny Of Parvalbumin Sequences In Jawed Vert...supporting
confidence: 87%
“…In teleost fish, five parvalbumin lineages can be readily distinguished by phylogenetic tree analysis (Figure 4 and Supplementary File S4): (1) the α-parvalbumins (pvalb6 and pvalb7); (2) the oncomodulins (pvalb8 and pvalb9); (3) the muscle parvalbumins pvalb1to-4; (4) pvalb5; and (5) pvalb10. These lineages were also observed in the phylogenetic tree analysis by Mukherjee et al, 2021 [26], who, like us, also found that phylogenetic tree analysis cannot properly distinguish between pvalb6 and pvalb7, between pvalb8 and pvalb9, and between pvalb1, -2, -3, and -4. This inability is probably caused by these molecules being generally well-conserved and having relatively few variable residues whose identities seem to somewhat "fluctuate around a conserved theme" rather than develop in a certain direction.…”
Section: The Parvalbumin Genes Map To Paralogous Regions That Derived...supporting
confidence: 82%
See 1 more Smart Citation
“…Parvalbumin (PVALB ) , a small calcium‐binding protein present in the muscles of vertebrates, is a known major fish allergen (Kuehn et al, 2014) and most fish allergic individuals have anti‐PVALB IgE. There are three main gene types (pvalb‐α, pvalb‐β1 , and pvalb‐β2) that appear highly diverse in teleost (Mukherjee et al, 2021). In leopard coral grouper ( Plectropomus Leopardus ), PVALB is among the highest gene expressed in muscle (Mekuchi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%